2022
DOI: 10.1587/elex.18.20210494
|View full text |Cite
|
Sign up to set email alerts
|

PAM4 48-Gbit/s wireless communication using a resonant tunneling diode in the 300-GHz band

Abstract: In modern optical communications, pulse amplitude modulation 4 (PAM4) is employed to achieve higher data rates than that achieved by conventional non-return-to-zero format. Meanwhile, there is an increasing interest to convert wired connections to wireless in data centers using high-speed millimeter-wave and terahertz (THz) links. Here, we introduced the PAM4 modulation for THz wireless communications using a resonant tunneling diode (RTD) receiver. Compared with a Schottky-barrier diode receiver, the RTD rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The degree of enhancement of sensitivity by coherent detection is dependent on the input power and up to about 40 dB gain compared to direct detection was demonstrated in reference [7]. The amplified‐detection mode is still under investigation but a further 6 dB gain in sensitivity was demonstrated in reference [8]. The downconverted IF band signal is amplified by an RF amplifier (29 dB gain and 40 GHz bandwidth), and fed into a broadband real‐time oscilloscope (RTO) (Keysight Technologies DSAZ634A) with 160 GSa/s sampling rate and 63 GHz analog bandwidth.…”
Section: Data Transmission Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of enhancement of sensitivity by coherent detection is dependent on the input power and up to about 40 dB gain compared to direct detection was demonstrated in reference [7]. The amplified‐detection mode is still under investigation but a further 6 dB gain in sensitivity was demonstrated in reference [8]. The downconverted IF band signal is amplified by an RF amplifier (29 dB gain and 40 GHz bandwidth), and fed into a broadband real‐time oscilloscope (RTO) (Keysight Technologies DSAZ634A) with 160 GSa/s sampling rate and 63 GHz analog bandwidth.…”
Section: Data Transmission Experimentsmentioning
confidence: 99%
“…At the Rx side, the wireless signal is downconverted to the IF band using the RTD. The RTD operated in the amplified‐detection mode (region (iii) in Figure 1), which combines the amplification and envelope‐detection capabilities [8]. The degree of enhancement of sensitivity by coherent detection is dependent on the input power and up to about 40 dB gain compared to direct detection was demonstrated in reference [7].…”
Section: Data Transmission Experimentsmentioning
confidence: 99%
“…RTDs are the highest frequency solid state electronic device with the fundamental frequency approaching 2 THz [13]. Its main limitation was low output power, typically in the microwatt range, but the technology is now producing THz powers in the milliwatt (mW) range, and therefore starting to enable practical applications in imaging, multi-gigabit wireless communication systems, and others [23][24][25][26]. A good review of the state-of-the-art of RTD THz technology can be found in [27].…”
Section: Thz Imagingmentioning
confidence: 99%
“…The RTD THz transceiver has been widely reported for next generation ultrahigh speed wireless communication system towards 100 Gbps [23][24][25]57,59]. The application of RTD technology in THz imaging systems and other non-destructive testing (NDT) applications is just emerging but is under fast development.…”
Section: Compact Rtd Thz Imaging and Other Ndt Systemsmentioning
confidence: 99%
“…Although mmWave transmitters have been realized based on Si-based and III-V technology platform, RTD-based mmWave technology demonstrates potential advan-tages in terms of simplicity, low-cost, and high sensitivity compared to other competing counterparts [2,3] . Therefore, to realize the mmWave wireless communication with large channel bandwidths and ultrahigh data rates, an mmWave transmitting link employing an RTD-based oscillator was proposed, as shown in Figure 1.…”
Section: ⅰ Introductionmentioning
confidence: 99%